Effect of the Cash Support from the Vision Umurenge Programme on Household Financial Behaviour in Rwanda: The Case of Direct Support (DS) - Emmanuel Munyemana; Charles Ruranga; Joseph K. Mung’atu (Economies)
This study aims to quantify the extent to which poor households receiving cash support from the Vision Umurenge Programme (VUP) allocate their income across major spending categories, mainly consumption, savings, household-level investment, and cash transfers for community participation. The analysis utilises a nationally representative panel dataset of 1642 respondents, collected between 2013 and 2017. A Maximum Likelihood Method (MLM) approach was employed to model four financial behaviours: (i) saving, (ii) consumption, (iii) investment, and (iv) social transfers as a proxy for community participation. The independent variables include the monetary benefits received by individuals over different periods, alongside demographic characteristics such as gender, age, education level, and area of residence (rural–urban), which were controlled in the analysis. The findings reveal a positive and statistically significant effect of the direct cash support provided by the VUP on increased consumption, and marginal effects on individual savings and investment behaviours. However, the data do not provide sufficient evidence to conclusively establish a relationship between participation in the VUP and cash transfers for community participation. The study recommends the intensification of efforts to engage in saving as way to build resilience, and further suggest a periodic increase in the VUP benefits’ size to cushion inflation effects.